THE RELATIONSHIP OF INTERLEUKIN-6 LEVELS AND THE DEGREE OF MYOPIA IN YOUNG ADULTS IN NORTH SUMATRA UNIVERSITY HOSPITAL - Hidayat, Salman Saisar; Amra, Aryani Atiyatul; Lubis, Rodiah Rahmawaty (Majalah Oftalmologi Indonesia, 2023)
Background. Myopia is one of the refractive errors where parallel light from infinity is focused in front of the retina without accommodation. Various cytokines have been implicated in the development of myopia, including interleukin-6 (IL6) and matrix metalloproteinase-2 (MMP-2). IL-6 is one of the pro-inflammatory cytokines that play a role in ocular disease pathology. Chronic subclinical inflammation may play a role in elongation of the eyeball, inflammation promotes the breakdown of the scleral extracellular matrix and results in axial elongation. Objective. To determine the relationship of interleukin-6 levels and the degree of myopia in young adults in North Sumatra University Hospital. Methods. This research is an analytic observational study with a case control design, held from February 2022. Primary and secondary data are collected from interviews and direct observation. Bivariate analysis of differences in interleukin-6 levels in myopia and emmetropia uses T-independent test, if the data are normally distributed. If the data are not normally distributed, then the Mann Whitney test is used. Bivariate analysis to analyze differences in interleukin-6 levels based on the degree of myopia uses the Kruskal Wallis test, followed by a post hoc test using the Mann Whitney test and t-independent. Results. A total sample consists of 30 patients who suffer from myopia and 30 control samples. The mean age in the myopia group was 28.87 years with the youngest age being 25 years and oldest age 34 years. Most of them are moderate myopia with 15 people (50%). There was no significant difference in interleukin-6 levels between myopia and control groups (p = 0.147). There was a difference in the mean level of interleukin-6 based on the degree of myopia (p = 0.005). Conclusions. There is an association between interleukin-6 levels and the degree of myopia in young adult patients. No differences in interleukin-6 levels were found significant between myopia and control groups.